Impact of cone-beam computed tomography with automated feeder detection software on the survival outcome of patients with hepatocellular carcinoma during treatment with conventional transarterial chemoembolization - Kittipitch Bannangkoon (BMC, 2021)
Abstract Background Inoperable hepatocellular carcinoma (HCC) is treated by conventional transarterial chemoembolization (cTACE) using cone-beam computed tomography (CBCT) or digital subtraction angiography (DSA). We compared patient survival outcomes between CBCT-cTACE with automated tumor-feeder detection (AFD) software and DSA-cTACE alone in inoperable HCC patients. Methods We reviewed the data of 337 HCC patients treated by CBCT-cTACE or DSA-cTACE between January 2015 and December 2019. Treatment response, progression-free survival (PFS), overall survival (OS), and complications between the CBCT-cTACE and DSA-cTACE groups were compared. Univariate and multivariate logistic regression analyses examined the potential prognostic factors affecting survival after chemoembolization. Results Tumor response rates in complete response, partial response, and stable disease at 1 month were 67%, 28%, and 4% in the CBCT-cTACE group and 22%, 48%, and 9% in the DSA-cTACE group, respectively. OS rates of patients in the CBCT-cTACE versus DSA-cTACE groups were 87% versus 54%, 44% versus 15%, and 34% versus 7% at 1, 3, and 5 years, respectively. The CBCT-cTACE group had significantly improved PFS (p < 0.001) and OS (p < 0.001). Multivariate analysis showed that CBCT with AFD software was an independent factor associated with longer OS (hazard ratio, 0.38; p < 0.001). Conclusions Compared with conventional DSA, combining selective cTACE with CBCT and AFD software leads to better tumor response and prolongs OS in patients with inoperable HCC.